1993
DOI: 10.1038/sj.bdj.4808327
|View full text |Cite
|
Sign up to set email alerts
|

The voluntary reflux phenomenon

Abstract: Dental erosion can be caused by recurrent contact with regurgitated gastric acid and there are a number of recognised conditions in which this can occur. A previously undescribed condition, which we have termed the 'voluntary reflux phenomenon', is described, and an illustrative case history given, together with details of several other similar cases. The condition may well be first recognised by the dentist, may have serious psychiatric implications, and has features which can help distinguish it from other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…This is an important finding since the palatal surfaces of upper incisor teeth are commonly affected in patients with dental erosion caused by intrinsic factors. 17 The experienced observers from Groningen had no obviously better reproducibility than the inexperienced observers from Sweden. However, the observer who contributed in both places performed better in Sweden, suggesting that the teeth used there may have positively influenced the reproducibility.…”
Section: Gmentioning
confidence: 99%
“…This is an important finding since the palatal surfaces of upper incisor teeth are commonly affected in patients with dental erosion caused by intrinsic factors. 17 The experienced observers from Groningen had no obviously better reproducibility than the inexperienced observers from Sweden. However, the observer who contributed in both places performed better in Sweden, suggesting that the teeth used there may have positively influenced the reproducibility.…”
Section: Gmentioning
confidence: 99%
“…It has also been suggested that it affects highly intelligent, professional people [110]. The pathophysiology of rumination is poorly understood and has been incompletely studied.…”
Section: Ruminationmentioning
confidence: 99%
“…Rumination is a condition when patients eat their food, swallow and then physically increase and decrease their diaphragmatic pressure and voluntarily regurgitate the food mixed with gastric acid into their mouths. Although first recognised in patients in long term care facilities it is also common in those patients with a similar psychological background as patients with eating disorders 27 . Patients with these signs and symptoms should not only receive dental care to protect their oral health, but a referral to a physician to assess their medical condition should be considered.…”
Section: Pathogenesismentioning
confidence: 99%